THEMATIC PROGRESSION USED IN ZAKIR NAIK'S LECTURE - Ike Tri Susanti; Ingatan Gulo (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2021)
One of the great importance of language is not only seen when it is applied on political speech, but it also represents as in the form of public speaking or public lecture. In that case, the objective of this research is to analyze the thematic progression of one of the public lectures in Oxford Union 2011, delivered by a famous lecturer and public speaker, Dr. Zakir Naik. In doing the analysis, there are many things that can be studied in a speech, especially when it is related with the analysis by using discourse analysis (DA). In doing the research, qualitative method is applied and the writers used Paltridge’s theory (2006) to analyze the thematic progression. As the result of the study, the writers found that from the total of 29 data, there are 11 data of reiteration or constant theme, 13 data of linear theme or zig-zag pattern and finally, 5 data that are categorized as multiple or split rheme. Therefore, the most dominant pattern expressed by Zakir Naik in his public lecturer is linear theme.